2020
DOI: 10.1097/eja.0000000000001379
|View full text |Cite
|
Sign up to set email alerts
|

The analgesic effectiveness of ilioinguinal-iliohypogastric block for caesarean delivery

Abstract: BACKGROUND An effective analgesia strategy following caesarean delivery should be designed to improve fetomaternal outcomes. Much recent research has focused on the efficacy of ilioinguinal-iliohypogastric (II-IH) block for providing such analgesia. DESIGN A systematic review and meta-analysis of randomised controlled trials. OBJECTIVES To investigate the effectiveness of II-IH block in patients undergoing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Third, there is now evidence from a meta-analysis and trial sequential analysis that the ilioinguinal iliohypogastric block is effective in reducing postoperative opioid consumption [6].…”
Section: Pre-operativelymentioning
confidence: 99%
“…Third, there is now evidence from a meta-analysis and trial sequential analysis that the ilioinguinal iliohypogastric block is effective in reducing postoperative opioid consumption [6].…”
Section: Pre-operativelymentioning
confidence: 99%
“…It has been shown that these blocks decrease pain scores and opioid consumption in the postoperative period in CD. 2,3…”
mentioning
confidence: 99%